2021
DOI: 10.1002/smsc.202100070
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic C–N Coupling for Urea Synthesis

Abstract: The industrial urea synthesis consists of two consecutive processes, nitrogen + hydrogen → ammonia followed by ammonia + carbon dioxide → urea. The electrocatalytic coupling of carbon source (carbon dioxide) and nitrogen source (nitrogen, nitrite, nitrate) by skipping the ammonia synthetic process might be a promising alternative to achieve the efficient urea synthesis; in this case, two industrial steps with high energy consumption and high pollution are optimized into one renewable energy‐driving electrocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 40 publications
1
85
0
Order By: Relevance
“…The electrosynthesis of urea has been proposed as a simple and onsite production method. We strongly advise the readers to read Kornienko's review on C-N construction by electrocatalysis [460] and Wang's review on C-N coupling for urea electrosynthesis [461]. Wang et al recently reported a breakthrough strategy for fixing N2/CO2 simultaneously for mild urea generation by electrocatalytically coupling two gaseous molecules, namely, N2 and CO2, into urea [462].…”
Section: C-n Coupling Reaction To Amide Urea and Amine (Methylamine)mentioning
confidence: 99%
“…The electrosynthesis of urea has been proposed as a simple and onsite production method. We strongly advise the readers to read Kornienko's review on C-N construction by electrocatalysis [460] and Wang's review on C-N coupling for urea electrosynthesis [461]. Wang et al recently reported a breakthrough strategy for fixing N2/CO2 simultaneously for mild urea generation by electrocatalytically coupling two gaseous molecules, namely, N2 and CO2, into urea [462].…”
Section: C-n Coupling Reaction To Amide Urea and Amine (Methylamine)mentioning
confidence: 99%
“…In industry, urea is synthesized from liquid ammonia and carbon dioxide under the conditions of high pressure and elevated temperature 3,4 . However, the current urea synthetic protocol suffers from high energy input and the consumption of value-added ammonia, far away from meeting the demands for sustainable development 5 . Consequently, the electrocatalytic urea synthesis has emerged as one of the promising alternatives for the traditional urea manufacture to realize the urea production under milder conditions [6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Consequently, the electrocatalytic urea synthesis has emerged as one of the promising alternatives for the traditional urea manufacture to realize the urea production under milder conditions [6][7][8][9][10][11] . Compared with the indirect method of initial ammonia production with subsequent urea synthesis, the direct urea synthesis from co-activation and coupling of carbon dioxide (CO 2 ) and nitrate (NO 3 − ) waste plays the crucial role in the development of urea synthetic processes, to close the global carbon footprint, maintain nitrogen balance and reform the urea industry simultaneously 5,12,13 .…”
mentioning
confidence: 99%
“…Electrocatalysis, which can be driven by renewable electricity to obtain value-added products under ambient conditions, is a technically viable and zero-carbon-emission route. Researchers have recently demonstrated the electrochemical synthesis of urea through the direct coupling of N 2 with CO 2 in water under ambient conditions. For instance, Wang et al reported the electrocatalytic synthesis of urea using PdCu–TiO 2 catalysts, where the electrocatalytic C–N coupling mechanism was studied systematically .…”
mentioning
confidence: 99%